Research on the Present Situation and Development of Anti-Harsh Environment Computer Technology - Ci, Jianping (Journal of Artificial Intelligence and Information, 2025)
Resilient computer technology is a technology developed to meet the computational requirements under harsh environmental conditions. Harsh environments present numerous challenges to computer technology, including high temperatures, low temperatures, humidity, vibrations, radiation, and electromagnetic interference. To address these challenges, various techniques have been applied to resilient computer technology, such as enclosed and sealed designs, as well as dust and waterproofing technologies. Looking ahead, the development trends of resilient computer technology encompass the application of new materials, improvements in chip and hardware technology, and the enhancement of intelligence and autonomy. These technological advancements will offer better solutions for computing and data processing in challenging environmental conditions.